The life of paper: letters and a poetics of living beyond captivity - Luk, Sharon (University of California Press, 2018)
Introduction : the life of paper -- The inventions of China -- Imagined genealogies (for all who cannot arrive) -- "Detained alien enemy mail : examined" -- Censorship and the/work of art, where they barbed the/fourth corner open -- Ephemeral value and disused commodities -- Uses of the profane